Thyroid‐on‐a‐Chip: An Organoid Platform for In Vitro Assessment of Endocrine Disruption (Adv. Healthcare Mater. 8/2023). Issue 8 (24th March 2023) - Carvalho, Daniel J.; Kip, Anna M.; Romitti, Mírian; Nazzari, Marta; Tegel, Andreas; Stich, Matthias; Krause, Christian; Caiment, Florian; Costagliola, Sabine; Moroni, Lorenzo; Giselbrecht, Stefan
Abstract : Thyroid Functionality Advanced 3D in vitro assays are urgently needed to better identify endocrine disrupting chemicals (EDCs) and their effects on the thyroid gland. Article 2201555 by Stefan Giselbrecht and co‐workers reports a novel organ‐on‐a‐chip system, which combines physiological thyroid organoids, reversibly sealed microdevices, and transcriptomic technologies for in vitro detection of EDCs.